Avaliação da atividade antitumoral in vitro e in vivo de novos complexos de rutênio contendo ácido salicílico e derivados - Popolin, Cecília Patricia (Universidade Federal de São Carlos, 2021)
Cancer is a term used for diseases in which abnormal cells divide uncontrolled, spread, and invade other tissues through the blood and lymphatic systems. Breast cancer is one of the most common and with higher mortality among women. Its heterogeneity represents a critical challenge in the clinic, as it requires specific treatment for each subtype of the disease. The treatments used for breast cancer have a high resistance rate and low selectivity for tumor cells, causing several side effects. The development of antitumor metal-based compounds started with the discovery of antitumor activity of cisplatin and is currently among the most widely used antitumor drugs in the clinic to treat various types of tumors, such as ovary, breast, head, and neck. Ruthenium complexes have attracted significant attention because they have unique properties that can justify their antitumor potential, such as mimicking the iron for binding several biomolecules, including transferrin and albumin, making it more specific to tumor cells. This work aimed to select among different complexes a new ruthenium complex, which would be the candidate for antitumor drug, and evaluate the effects of the selected complex through in vitro studies on breast cells and in vivo through the spontaneous metastases of syngenic an orthotopic model. The results demonstrated that the complex Ru(Amsal) was the most selective against breast tumor cells MDA-MB-231 among the six complexes tested. Morphological studies showed that the Ru(Amsal) complex promoted more significant changes in the morphology of breast cancer cells MDA-MB-231 compared to other cell lines tested and, besides, the complex was able to act in the colony formation process, reducing the number and size of the colonies. In the metastatic cascade assays, the complex Ru(Amsal) inhibited migration, invasion, and take and altered the organization of the cytoskeleton of breast cancer cells MDA-MB-231. The complex also induced cell death by apoptosis, DNA damage, nuclear fragmentation, and mitochondrial membrane potential depolarization. Furthermore, it changed the cell cycle of breast tumor cells MDA-MB-231, increasing the percentage of these cells in the sub-G1 phase. An analysis of the effect of the complex Ru(Amsal) synthesized on a microemulsion (Ru(Amsal)ME) in vivo in a spontaneous metastases syngenic and orthotopic model demonstrated that this complex was able to inhibit pulmonary and bone metastases. Also, there were no signs of acute toxicity in animals treated with the complex. Therefore, the results indicate that the complex Ru(Amsal) has promising properties and might be a good alternative drug for breast cancer treatment.
Evaluation of in vitro and in vivo antitumor activity of new ruthenium complexes containing salicylic acid and derivatives
Keywords: Câncer; Câncer de mama; Complexos de rutênio; Apoptose; Metástase; Cancer; Breast cancer; Ruthenium complex; Apoptosis; Metastasis; CIENCIAS BIOLOGICAS::BIOLOGIA GERAL